Atrial arrhythmias associated with anti-tumor drugs in patients with malignant tumors and type 2 diabetes mellitus - Zhang, Beibei; Zhang, Lei; Ren, Yili; Xu, Chenkai (Frontiers in Oncology, 2025)
ObjectivePatients with malignancies and type 2 diabetes mellitus (T2DM) face heightened risks of cardiotoxicity from antitumor therapies, yet the interplay between diabetes, antitumor drugs, and atrial arrhythmias remains underexplored. This study investigates the incidence and risk factors of atrial arrhythmias in this high-risk populationMethodsIn this retrospective cohort study, 171 patients with T2DM and malignancies receiving antitumor therapy at Zhejiang Hospital (January 2022–January 2024) were analyzed. Serial 12-lead electrocardiograms (ECGs) were performed pre- and post-chemotherapy cycles to detect new-onset atrial arrhythmias. Multivariate Cox regression identified risk factors, adjusting for age, hypertension, renal function, and cardiac biomarkers (troponin I, NT-proBNP). Subgroup analyses stratified by tumor type, diabetes duration, and drug class were conducted.ResultsAtrial arrhythmias occurred in 10.5% of patients (18/171), with a significantly higher incidence in diabetics versus non-diabetics (18.4% vs. 4.2%, P=0.004). Advanced age (HR=10.25, 95% CI 1.01–104.56; P=0.049) and anthracycline use (HR=2.70, 95% CI 1.02–7.19; P=0.045) independently predicted arrhythmia risk. Diabetes duration ≥5 years (HR=2.85, 95% CI 1.22–6.70; P=0.016) and reduced eGFR (<60 mL/min/1.73m²; HR=2.58, 95% CI 1.04–6.39; P=0.039) further elevated risk. A synergistic interaction was observed between diabetes and anthracyclines (HR=3.95, 95% CI 1.58–9.85; P=0.002). Dynamic rises in NT-proBNP (≥50%) and troponin I (≥5 ng/L) emerged as strong predictors (HR=2.11 and 2.73, respectively; P<0.05).ConclusionT2DM significantly amplifies atrial arrhythmia risk in cancer patients receiving antitumor drugs, particularly anthracyclines. Age, ischemic heart disease, and biomarker trends are critical risk indicators. Proactive ECG and biomarker monitoring, coupled with cardio-oncology collaboration, are essential for mitigating arrhythmia-related morbidity.